先化简,后求值 (a+2b)²-(a-b)(a-4b),其中a=1/3,b=2
1个回答
(a+2b)^2-(a-b)(a-4b)
=a^2+4b^2+4ab-a^2+5ab-4b^2
=9ab
=9*1/3*2
=6
相关问题
先化简后求值:[4(a+b)(a-b)-(2a-b)]+3ab,其中a=1/2,
先化简,后求值(2a-b)(2a+b)+(2a-b)(b-4a)+(b-3a)^2,其中a=-1,b=-2
先化简,后求值(a+b)(a-b)+b(b-2),其中a=-2,b=--1
先化简,再求值:(a-b)(a-2b)-(3a-2b)(a-3b),其中a=4,b=-1
先化简,再求值:a+2b/a+b+2b²/a²-b²,其中a=-2,b=3/1
先化简,再求值:4(a+b)(a-b)+[-2(a+b)]²+(a-b),其中a=1/2,b=-1/2.
先化简再求值 (3a+2b)(3a-3b)-(a-2b)(2a-b),其中a=-1.5,b=1/4
先化简,再求值:(2a+b)(2a-b)+3(2a-b)2+3a(4a-3b),其中a=-1,b=2.
先化简再求值(2a+b)(2a-b)+3(2a-b)^2+(-3a)(4a-3b)其中a=-1,b=-2
先化简,再求值:(a+b)(a-b)+(a+b)2-2a2,其中a=3,b=-[1/3].